Isolation and Characterization of Yeasts Able to Assimilate Sugarcane Bagasse Hemicellulosic Hydrolysate and Produce Xylitol Associated with Veturius transversus (Passalidae, Coleoptera, and Insecta) - Italo Thiago Silveira Rocha Matos; Enedina Nogueira Assunção; Edson Junior do Carmo; Verena Makaren Soares; Spartaco Astolfi-Filho (International Journal of Microbiology)
Yeasts are an important component of insect gut microbial content, playing roles such as degradation of polymers and toxic compounds, biological control, and hormone, vitamin, and digestive enzyme production. The xylophagous beetle gut is a hyperdiverse habitat and a potential source of new species with industrial abilities such as enzyme production, pentose fermentation, and biodetoxification. In this work, samples of Veturius transversus (Passalidae, Coleoptera, and Insecta) were collected from the Central Amazon Rainforest. Their guts were dissected and a total of 20 microbial colonies were isolated using sugarcane bagasse hemicellulosic hydrolysate. They were identified as having 10 distinct biochemical profiles, and genetic analysis allowed identification as three clades in the genera Candida, Williopsis, and Geotrichum. All colonies were able to assimilate D-xylose and 18 were able to produce xylitol, especially a strain of Geotrichum, with a maximum yield of 0.502 g·g−1. These results agree with a previous prediction that the microbial community associated with xylophagous insects is a promising source of species of biotechnological interest.